Linkage Inc.'s best practices in leadership development handbook case studies, instruments, training - edited by David Giber (San Francisco Pfeiffer, 2009)
Leadership development is a planned effort that enhances the learner's capacity to lead people. Building on the success of the first edition, Linkage conducted a study of over 300 top organizations and their needs in organizational change and leadership development that identifies approaches to leadership development that have proven to be successful. The work offers practical "how-to" instructions developing leaders and engaging in leadership development. It provides current in-depth models, assessments, tools, and other instruments that can be used for immediate application within a variety of organizations.
Includes bibliographical references (p. 433-437) and index.
Keywords: Leadership--Case studies